2021
DOI: 10.3390/jcm10194446
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Role of Chronic Rhinosinusitis in Acute Ischemic Stroke Patients Undergoing Mechanical Thrombectomy

Abstract: Background: The aim of the study was to assess the relevance of chronic rhinosinusitis (CRS) CT features to the efficacy of mechanical thrombectomy (MT) in patients with acute ischemic stroke. Methods: This study included 311 patients qualified for MT in whom the CRS features were assessed based on a CT scan, according to the Lund-Mackay (L-M) score. Clinical, inflammatory parameters, patients neurological (NIHSS) and functional status (mRS), and recanalisation efficacy (TICI) were compared between patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Ref. [20] is devoted to assessing the relevance of chronic rhinosinusitis CT features to the efficacy of mechanical thrombectomy in patients with acute ischemic stroke. To do this, the study included 311 patients qualified for mechanical thrombectomy in whom the chronic rhinosinusitis features were assessed based on a CT scan, according to the Lund-Mackay score.…”
Section: Current Research Analysismentioning
confidence: 99%
“…Ref. [20] is devoted to assessing the relevance of chronic rhinosinusitis CT features to the efficacy of mechanical thrombectomy in patients with acute ischemic stroke. To do this, the study included 311 patients qualified for mechanical thrombectomy in whom the chronic rhinosinusitis features were assessed based on a CT scan, according to the Lund-Mackay score.…”
Section: Current Research Analysismentioning
confidence: 99%
“…On the contrary, Lee et al showed that CRS patients under 60 years of age were at greater risk of stroke [ 3 ]. Moreover, the impact of CRS on the short-term prognosis in stroke patients has also been confirmed [ 15 ]. The neurological status in patients with mild signs of CRS, as evaluated with CT scans, was significantly better than in those with moderate or severe lesions.…”
Section: Reviewmentioning
confidence: 99%
“…As a result, the authors proposed the CT features of CRS as an early prognostic tool for patients with ischemic stroke. Notably, when moderate or severe CRS is diagnosed, intensive maximal medical therapy or interventional treatment should be started as early as possible, as this may improve the short-term efficacy of endovascular treatment of patients with stroke [ 15 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation